Polityka przestrzenna powiatu - możliwości i ograniczenia (studium na podstawie powiatów województwa lubelskiego) - Gorzym-Witkowski, Waldemar A. (Spatial Policy for a District - Opportunities and Constraints (Study of the Districts of Lublin Province), 2008)
The district is perceived as the weakest level of Polish self-government. However, it is vested with a number of powers related to spatial policy. Obligations regarding, among others, road engineering, natural environment protection or forest economics, significantly affect the space. Therefore it is necessary to create and maintain a coherent spatial policy. Numerous districts try to formulate such a policy within their development strategies. However, effective implementation of the spatial policy is very difficult. The principal reason of this is the weak position of the district within the spatial planning system. The important reason is also the shortage of the district budgets, only slightly changed after the accession of Poland to the EU. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 297-304